Instructional practices in the teaching of literature: what matters? - Mustakim, Siti Salina; Lebar, Othman; Minghat, Asnul Dahar (Human Resource Management Academic Research Society, 2018)
The primary aim of the study was to assess the instructional practices employed by teachers in classroom instruction in teaching of literature. In order to enhance, develop and explore in-depth the utilization of approaches and activities in teaching, three models for teaching literature were incorporated in the study. They are (1) The Cultural Model, (2) The Language Model, and (3) The Personal Growth Model. Six approaches and activities in the teaching of literature were listed as indicators investigated during the study; language based, paraphrastic, information-based, personal response, moral-philosophical, and stylistic. Findings indicated, firstly, that there was an inconsistency in the utilization of approaches and activities during teaching. Secondly, students dependency on the development of portfolio was the major contribution towards students’ moderate development in learning. Thirdly, the instructional practices employed were mainly focusing on technical components of reading, writing, listening, and speaking as opposed to the teaching of literature.